Penerapan Metode SAW Untuk Pemberian Bonus Tahunan Berdasarkan Kinerja Karyawan - Jeperson Hutahaean; William Ramdhan; Sartini Sartini (STMIK Budi Darma, 2022)
Perkebunan Nusantara III (PTPN III) Mambang Muda North Labuhan Batu Regency is one of 14 Plantation State-Owned Enterprises (BUMN) engaged in plantation business, processing and marketing of plantation products. The Company's business activities include cultivating and processing oil palm and rubber plants. In the world, Sumatra is known as a producer of high-quality rubber, more than 38,000 hectares of PTPN III Mambang Muda rubber land in Labuhan Batu Utara Regency are endeavored to produce the best quality latex in the world. Behind the production of quality sap, reliable employees are needed in processing the sap, therefore PTPN III Mambang Muda must provide an annual bonus in addition to the basic salary to boost the performance and work productivity of its employees. However, the problem that occurred at PTPN III Mambang Muda was that it could not estimate the amount of the bonus correctly in giving the annual employee bonus because there were no criteria in staff who had priority to get a salary bonus including work performance, work discipline, and years of service. using conventional systems, the closeness of managers to employees often results in decisions that are different from what they should be, this causes the results of the decisions to be incorrect. The method used in decision support for granting annual bonuses to employees is the Simple Additive Weighting method because this method can select staff from various other alternatives who are entitled to receive bonuses from the company which results from this study are able to rank employees of PTPN III Mambang Muda Labuhan Batu Utara Regency. Employees who get bonuses are employees with the top 3 scores, namely: Rudiadi with a score of 0.788235, Zulkarnaen with a score of 0.776471, and Arif Sitorus with a score of 0.752941